A biomimetic composite membrane for human thermal management and its preparation method and application
Patent Information
- Application Number
- CN202411399356.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-10-09
AI Technical Summary
相变材料是相变储热技术的核心,也是相变储热系统中最关键的部件之一,然而,在相变过程中易发生渗漏,且储能效率低,难以实现个性化温度调节
[0024](1)本发明利用球磨工艺对镓铟合金进行表面处理,去除其表面氧化层,且为防止镓铟合金氧化问题,球磨前向体系中加入吐温80以及硫代苹果酸制备得到稳定的经预处理的镓铟合金,有利于在聚乳酸PLA纤维上形成表面串珠形貌,有效提高了复合膜对太阳光的吸收能力,增强光热转换效果;同时,通过预处理消除了界面效应,增强了纤维膜的强度。
Smart Images

Figure CN119465510B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials synthesis technology, and in particular relates to a biomimetic composite membrane for human body thermal management, its preparation method and application. Background Technology
[0002] Maintaining thermal comfort for the human body in various environments is crucial for ensuring the normal functioning of human production activities. When the ambient temperature drops, human body temperature depends primarily on clothing, air conditioning, and the combustion of fossil fuels. However, with the widespread use of air conditioning and fossil fuels, we face an increasingly severe energy crisis and global warming. Driven by the demands for energy conservation, reduced consumption, and enhanced warmth, individual thermal management—which allows for wide-range regulation of the human microenvironment and precise heating of non-centralized living spaces—has become a current research hotspot. Utilizing renewable energy as a substitute for fossil fuels is essential for solving energy and environmental problems. Among these, solar energy, with its largest reserves, zero pollution, and wide availability, is the most promising fossil fuel alternative. The hope is that by leveraging solar energy and utilizing fabrics themselves to create a comfortable environment, it can replace the current energy-intensive indoor air conditioning and enable personalized temperature regulation through flexible wearable devices.
[0003] Phase change materials (PCMs), as energy storage media, can undergo phase change at near-isothermal temperatures, simultaneously storing or releasing energy to achieve efficient energy utilization and reduce CO2 emissions. PCMs are the core of phase change thermal energy storage technology and one of the most critical components in phase change thermal energy storage systems. However, they are prone to leakage during the phase change process, have low energy storage efficiency, and are difficult to regulate to a personalized temperature. Summary of the Invention
[0004] In view of the above-mentioned problems in the prior art, the present invention provides a biomimetic composite membrane for human body thermal management, its preparation method and application, which can improve the photothermal conversion efficiency of the composite membrane and provide excellent energy storage and heat preservation performance.
[0005] To achieve the above objectives, the technical solution provided by the present invention is as follows:
[0006] In a first aspect, this application provides a method for preparing a biomimetic composite membrane for human thermal management, comprising the following steps:
[0007] S1: Polylactic acid and pretreated gallium-indium alloy are dissolved in organic solvent A to obtain a first solution; phase change material is dissolved in organic solvent B to obtain a second solution; polyvinyl alcohol is dissolved in organic solvent C to obtain a third solution;
[0008] S2: Electrospinning is performed to prepare nanofiber membranes using the first solution as the outer layer solution, the second solution as the first inner layer solution, and the third solution as the second inner layer solution.
[0009] S3: The nanofiber membrane is immersed in deionized water and then freeze-dried to obtain the biomimetic composite membrane.
[0010] Optionally, the preparation of the pretreated gallium-indium alloy includes the following steps: adding the gallium-indium alloy into a ball mill jar, adding Tween 80 and thiomalic acid to it, and ball milling it in an organic solvent D for 3-8 h, wherein the organic solvent D is tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide or N,N-dimethylformamide.
[0011] Optionally, the organic solvent A is dichloromethane and N,N-dimethylformamide, and the volume ratio of dichloromethane to N,N-dimethylformamide is (4-6):2.
[0012] Optionally, the ball milling time is 6 hours.
[0013] Optionally, the propulsion speed of the outer layer solution is 2-6 mL / h, the propulsion speed of the outer layer solution in the electrospinning is 2-5 times that of the first inner layer, and the outflow speed of the outer layer solution is 2-5 times that of the second inner layer.
[0014] Optionally, S3 specifically includes: first drying the nanofiber membrane in a vacuum oven at 40-60°C; then ultrasonically immersing it in deionized water to remove polyvinyl alcohol; and finally freeze-drying it.
[0015] Optionally, the mass ratio of polylactic acid to gallium indium alloy raw material is (2-3):1.
[0016] Optionally, the phase change material includes paraffin wax, and the organic solvent B is a non-polar solvent, such as gasoline, kerosene, toluene, or xylene.
[0017] Optionally, the volume ratio of phase change material to solvent B is 1:(1.5-3).
[0018] Optionally, the mass-to-volume ratio of polyvinyl alcohol to organic solvent C is (2-5):100 g / mL, wherein the organic solvent C is dimethyl sulfoxide.
[0019] Optionally, the paraffin is pre-modified by mixing it with dodecane and tridecane at 30-45°C and then cooling it at 15-25°C.
[0020] Optionally, the ratio of the amount of thiomalic acid added to the mass of gallium indium alloy is (0.05-0.2):1, and the ratio of the amount of Tween 80 added to the mass of gallium indium alloy is (0.3-0.6):1.
[0021] Secondly, this application also provides a biomimetic composite membrane for human body thermal management, which is prepared by the preparation method described in the first aspect.
[0022] Thirdly, this application also provides the application of the biomimetic composite membrane described in the second aspect in human body thermal management.
[0023] Compared with the prior art, this application has at least the following beneficial effects:
[0024] (1) The present invention uses ball milling to treat the surface of gallium indium alloy to remove its surface oxide layer. In order to prevent the oxidation of gallium indium alloy, Tween 80 and thiomalic acid are added to the ball milling system to prepare a stable pretreated gallium indium alloy, which is beneficial to form a beaded morphology on polylactic acid (PLA) fibers, effectively improving the absorption capacity of the composite film to sunlight and enhancing the photothermal conversion effect. At the same time, the pretreatment eliminates the interface effect and enhances the strength of the fiber film.
[0025] (2) By efficiently encapsulating paraffin through multi-fluid spinning, leakage of phase change materials is avoided and energy storage characteristics are improved; and the creation of an internal hollow morphology gives the material thermal insulation properties, improving wearing comfort, and has broad application prospects in the field of human body thermal management materials. Attached Figure Description
[0026] Figure 1 This is a schematic diagram showing the morphology test results of the pretreated gallium-indium alloy in Example 1, where a is an electron microscope image; b is a grain size distribution map;
[0027] Figure 2 Electron micrograph of the morphology of the biomimetic composite film prepared in Example 1;
[0028] Figure 3 Schematic diagram of temperature and time changes of the biomimetic composite membranes prepared in Examples 1 and 2;
[0029] Figure 4 A schematic diagram of a thermal image recorded by an infrared camera when the biomimetic composite film prepared in Example 1 is transferred from light to shade.
[0030] Figure 5 This is a schematic diagram of a thermal image recorded by an infrared camera after the biomimetic composite membrane prepared in Example 1 was worn on a human body indoors. Detailed Implementation
[0031] The present invention will now be described in further detail with reference to the accompanying drawings:
[0032] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.
[0033] All reagents and materials used in this example can be purchased routinely. The quantitative experiments involved in the examples were all repeated at least three times, and the results were averaged.
[0034] Raw material source:
[0035] Gallium-indium alloy: purchased from Shenyang Jiabei Trading Co., Ltd.; its composition is: gallium 75wt%, indium 25wt%.
[0036] Paraffin wax was purchased from Dongguan Shengbang Polymer Materials Co., Ltd.
[0037] Example 1
[0038] A method for preparing a biomimetic composite membrane for human body thermal management, comprising the following specific steps:
[0039] Step 1: Add 15 ml of tetrahydrofuran (THF) to a 100 ml zirconium jar containing 75 zirconium balls (60 with a diameter of 6 mm and 15 with a diameter of 10 mm). Then, add 2 g of gallium-indium alloy raw material, 0.2 g of thiomalic acid, and 1 g of Tween 80 in a specific ratio. Run the mixture in a QM-3SPO4 planetary ball mill at 480 rpm for 6 hours to obtain the pretreated gallium-indium alloy.
[0040] Dissolve 0.8g of polylactic acid (PLA) particles in a mixed solution of 5ml dichloromethane and 2ml N,N-dimethylformamide, and add 3ml of pretreated gallium indium alloy to the solution according to a 7:3 ratio of gallium indium alloy raw material to PLA to prepare the first solution.
[0041] Kerosene and paraffin were mixed in a volume ratio of 2:1 to obtain a second solution;
[0042] Polyvinyl alcohol and dimethyl sulfoxide were mixed at a ratio of 3g:100mL to obtain a third solution.
[0043] Step 2: The first, second, and third solutions were added to syringes respectively. Spinning was performed using a 15G / 25G-25G three-fluid electrospinning needle, and the nanofibers were collected using a cylindrical metal roller with a diameter of 8 cm and a width of 20 cm. The electrospinning parameters were set as follows: applied voltage of 22 kV, outer layer solution advance speed of 4 mL / h, and advance speeds of the two inner layer solutions of 1.3 mL / h each. The distance between the syringe needle tip and the collecting roller was maintained at 15 cm. After electrospinning for 120 minutes, the uniformly thick nanofiber fabric collected was the nanofiber membrane.
[0044] Step 3: The nanofiber membrane was dried in a vacuum oven at 40°C for 24 hours, then ultrasonically treated in deionized water and soaked for 48 hours to remove the internal polyvinyl alcohol (PVA). Finally, it was freeze-dried for 48 hours to obtain a biomimetic composite membrane with a composite morphology.
[0045] Example 2
[0046] Step 1: Dissolve 0.8g of polylactic acid (PLA) particles in a mixed solution of 5ml dichloromethane and 2ml N,N-dimethylformamide to obtain the first solution;
[0047] Kerosene and paraffin were mixed in a volume ratio of 2:1 to obtain a second solution.
[0048] Step 2: The first and second solutions were added to syringes respectively. Spinning was performed using a 15G / 25G-25G dual-fluid electrospinning needle, and the nanofibers were collected using a cylindrical metal roller with a diameter of 8 cm and a width of 20 cm. The electrospinning parameters were set as follows: applied voltage of 22 kV, outer layer solution advance speed of 4 mL / h, inner layer solution advance speed of 1.3 mL / h, and the distance between the syringe needle tip and the collecting roller was maintained at 15 cm. After electrospinning for 120 minutes, the uniformly thick nanofiber fabric collected was the nanofiber membrane.
[0049] Step 3: Dry the nanofiber membrane in a vacuum oven at 40°C for 24 hours to obtain the biomimetic composite membrane.
[0050] Table 1 shows the photothermal conversion efficiency and energy storage characteristics of the phase change thin film materials prepared in Examples 1 and 2. It can be seen that the performance of the biomimetic composite film obtained in this application is significantly improved compared with that of Example 2.
[0051] Table 1 Performance Comparison of Composite Membranes
[0052] Example 1 53.6% 89.7 Example 2 42.3% 76.1
[0053] Figure 1 The image shows the morphological characteristics of the pretreated gallium-indium alloy under electron microscopy. (From...) Figure 1 As can be seen from a, the gallium-indium alloy has a relatively uniform particle size after ball milling. Figure 1 The particle size distribution diagram given in b shows that the average size of the gallium-indium alloy is greater than 2 μm, and it can form a distinct beaded morphology on the fiber (e.g., Figure 2 Experiments have shown that when the ball milling time is too short, the particle size is too large, which reduces the strength of the fiber membrane. When the ball milling time is too long, the beaded morphology on the fiber is formed very slowly, which is not conducive to improving the photothermal conversion efficiency. The optimal ball milling time is 6 hours, which can obtain both high fiber strength and is conducive to photothermal conversion.
[0054] from Figure 2 SEM images of the cross-sections show that the solid fibers are encapsulated in paraffin wax, and most of the solid fibers exhibit a hollow morphology. This result indicates that we have successfully fabricated a composite morphology of surface gallium-indium alloy beads with a hollow interior.
[0055] Figure 3 a, Figure 3b corresponds to the temperature-time cycling graphs of the biomimetic composite films prepared in Examples 1 and 2, respectively. Under simulated solar radiation of 100 mW / cm² using a xenon lamp, the temperature of the biomimetic composite film gradually increased over time, reaching saturation within a certain period. Then, the xenon lamp was turned off to begin cooling. Both examples exhibited a plateau during the cooling process, which is due to the heat absorbed by the melting of paraffin during heating and the subsequent release of heat during crystallization during cooling. Comparison shows that the saturation temperature of Example 1 is slightly higher than that of Example 2, and the exothermic plateau is more pronounced. The beaded morphology on the gallium-indium alloy surface endows the biomimetic composite film with strong light absorption and excellent photothermal conversion performance, improving its energy storage efficiency. Ten photothermal cycling experiments demonstrate its excellent photothermal cycling stability.
[0056] Figure 4 The image shows a thermal image of the biomimetic composite film obtained in Example 1 during actual wear, recorded by an infrared camera. Under sunlight (outdoor temperature 30°C), the temperature of the biomimetic composite film rapidly rises to 47°C, far exceeding the skin surface temperature of 36.6°C, demonstrating its rapid photothermal response. Figure 4 a; Transfer the human body from sunlight to a cool place (around 15℃), recording the moment of transfer as time 0. Then, test the surface temperature of the composite membrane after different transfer times (the blank control group did not have the composite membrane, and the surface temperature was measured). The results are as follows: Figure 4 As shown in b, c, and d, the temperature of the blank control group dropped rapidly due to the disappearance of light. However, when the biomimetic composite membrane was installed, the energy released by the energy storage material inside the membrane provided warmth to the human body. Therefore, the surface temperature of the biomimetic composite membrane dropped slowly in the early stage and then the temperature remained stable for a period of time. After ten minutes of testing, the surface temperature of the membrane material with the biomimetic composite membrane was still maintained at around 34.5℃.
[0057] In addition, the thermal insulation performance of the biomimetic composite membrane obtained in Example 1 was tested (at which time there was no energy storage in the biomimetic composite membrane). After the human body temperature reached equilibrium in an indoor environment (around 25°C) (body surface temperature 35°C), the biomimetic composite membrane was worn on the human body at time 0 (as a control group, where the body surface temperature of the unworn group was measured). The surface temperature of the biomimetic composite membrane was measured after different time periods, and the results are as follows. Figure 5 As shown, due to the hollow morphology that allows a large amount of air to fill the fiber interior, the biomimetic composite membrane can prevent the dissipation of human body heat, resulting in a warming effect (as evidenced by the lower surface temperature of the composite membrane compared to the control group, the composite membrane effectively blocks heat dissipation into the air). The phase change biomimetic composite membrane with gallium-indium alloy surface beads and an internal hollow composite morphology prepared in this invention can provide continuous warmth to the human body and effectively prevent the loss of its own heat during outdoor testing.
[0058] Example 3
[0059] Modified paraffin wax is obtained by blending paraffin wax with dodecane and tridecane in different proportions. This allows for alteration of the phase transition temperature (PW) of the paraffin wax, enabling wide-range PW temperature control to meet individual temperature requirements. In this embodiment, modified paraffin wax is used as a PW material in the preparation of a radioactive composite membrane.
[0060] 0.5g of raw paraffin wax was melted in an oven. Separately, 1g of dodecane and 0.5g of tridecane were preheated to 35°C. After preheating, the melted paraffin wax was heated in a 37°C water bath and mixed with the dodecane and tridecane, and stirred for 1 hour. The mixture was then cooled to room temperature to obtain modified paraffin wax. Its phase transition temperature range was determined to be 20-30°C by DSC. The method described in this example allows for the control of the phase transition temperature range of the phase change material.
Claims
1. A method for preparing a biomimetic composite membrane for human body thermal management, characterized in that, Includes the following steps: S1: Polylactic acid and pretreated gallium-indium alloy are dissolved in organic solvent A to obtain a first solution; phase change material is dissolved in organic solvent B to obtain a second solution; polyvinyl alcohol is dissolved in organic solvent C as a third solution; the preparation of the pretreated gallium-indium alloy includes the following steps: adding gallium-indium alloy to a ball mill jar, adding Tween 80 and thiomalic acid to the ball mill jar, and ball milling in organic solvent D for 3-8 h; the ratio of the amount of thiomalic acid added to the mass of gallium-indium alloy is (0.05-0.2):1, and the ratio of the amount of Tween 80 added to the mass of gallium-indium alloy is (0.3-0.6):1; S2: Using the first solution as the outer layer solution, the second solution as the first inner layer solution, and the third solution as the second inner layer solution, a three-fluid electrospinning needle is used to prepare a nanofiber membrane by electrospinning. S3: First, the nanofiber membrane is dried in a vacuum oven at 40-60°C; then, it is ultrasonically soaked in deionized water to remove polyvinyl alcohol, and finally, it is freeze-dried to obtain the biomimetic composite membrane.
2. The method for preparing the biomimetic composite membrane for human body thermal management according to claim 1, characterized in that, The outer layer solution is propelled at a speed of 2-6 mL / h. In the electrospinning process, the outer layer solution is propelled at a speed 2-5 times that of the first inner layer, and the outer layer solution exits at a speed 2-5 times that of the second inner layer.
3. The method for preparing the biomimetic composite membrane for human body thermal management according to claim 1, characterized in that, The mass ratio of polylactic acid to gallium indium alloy raw material is (2-3):
1.
4. The method for preparing the biomimetic composite membrane for human body thermal management according to claim 1, characterized in that, The phase change material includes paraffin wax, and organic solvent B is a non-polar solvent.
5. The method for preparing the biomimetic composite membrane for human body thermal management according to claim 4, characterized in that, Paraffin wax is pre-modified as follows: Paraffin wax is mixed with dodecane and tridecane at 30-45°C and then cooled at 15-25°C.
6. A biomimetic composite membrane for human body thermal management, characterized in that, It is prepared by any one of the preparation methods according to claims 1-5.
7. The application of the biomimetic composite membrane as described in claim 6 in human body thermal management.
Citation Information
Patent Citations
Polylactic acid-gallium indium alloy adhesive material based on electrostatic spinning as well as preparation and application of polylactic acid-gallium indium alloy adhesive material
CN116657327A
Ultrahigh molecular weight polyvinyl coaxial phase change energy storage fiber and preparation method thereof
CN117626470A
Conjugated fiber and method of producing hollow fiber by using the conjugated fiber
JP2002173831A